Learning from Mistakes — A Comprehensive Study on Real World Concurrency Bug Characteristics - Lu, Shan; Park, Soyeon; Seo, Eunsoo; Zhou, Yuanyuan (2008 Architectural Support for Programming Languages and Operating Systems, 2008)
The reality of multi-core hardware has made concurrent programs pervasive. Unfortunately, writing correct concurrent programs is difficult. Addressing this challenge requires advances in multiple directions, including concurrency bug detection, concurrent program testing, concurrent programming model design, etc. Designing effective techniques in all these directions will significantly benefit from a deep understanding of real-world concurrency bug characteristics. This paper provides the first (to the best of our knowledge) comprehensive real world concurrency bug characteristic study. Specifically, we have carefully examined concurrency bug patterns, manifestation, and fix strategies of 105 randomly selected real world concurrency bugs from 4 representative server and client opensource applications (MySQL, Apache, Mozilla and OpenOffice). Our study reveals several interesting findings and provides useful guidance for concurrency bug detection, testing, and concurrent programming language design. Some of our findings are as follows: (1) Around one third of the examined non-deadlock concurrency bugs are caused by violation to programmers' order intentions, which may not be easily expressed via synchronization primitives like locks and transactional memories; (2) Around 34% of the examined non-deadlock concurrency bugs involve multiple variables, which are not well addressed by existing bug detection tools; (3) About 92% of the examined concurrency bugs can be reliably triggered by enforcing certain orders among no more than 4 memory accesses. This indicates that testing concurrent programs can target at exploring possible orders among every small group of memory accesses, instead of among all memory accesses; (4) About 73% of the examined non-deadlock concurrency bugs were not fixed by simply adding or changing locks, and many of the fixes were not correct at the first try, indicating the difficulty of reasoning concurrent execution by programmers.